Inhibition Kinetic Spectrophotometric Determination of Resorcinol Based on Its Inhibitory Effect on Formaldehyde Catalyzed Reaction Between Bromate and Spadns - Keyvanfard, Mohsen (Asian Journal of Chemistry, 2010)
A new, sensitive, simple, inexpensive and fast kinetic spectrophotometric method was developed for the determination of trace amounts of resorcinol over the range of 0.02-1.40 μg/mL.The method is based on the inhibitory effect of resorcinol on the formaldehyde catalyzed oxidation reaction of of spadns by bromate in acidic media is reported. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of spadns at 530 nm with a fixed-time 0.5-3.0 min from initiation of the reaction. The detection limit is 15.2 ng/mL and relative standard deviation of 0.4 and 1.2 μg/mL resorcinol for 5 replicate measurements was 2.2 and 2.7 %, respectively. The method was applied to the determination of resorcinol in water samples.